High-performance triboelectric nanogenerators incorporating chlorinated zeolitic imidazolate frameworks with topologically tunable dielectric and surface adhesion properties - Ye, J; Tan, JC (Elsevier, 2023)
Triboelectric nanogenerator (TENG), a device that can convert mechanical energy into electricity based on the principle of triboelectrification, has gained tremendous attention since its first discovery in 2012. Although TENG has versatile applications in energy harvesting and self-powered sensing, its commercialization is still limited by the low power output. Recently, metal-organic frameworks (MOFs), with their large surface area and excellent tunability, have been explored to enhance the electrical performance of TENG. Herein, we synthesized nanoparticles of hydrophobic zeolitic imidazolate framework ZIF-71 (RHO topology) and its non-porous counterpart ZIF-72 (LCS topology), which were subsequently incorporated in a polydimethylsiloxane (PDMS) matrix as filler materials. By modifying the topology of ZIF nanofillers, we found the dielectric constant and surface adhesion of composites are both enhanced, thereby generating significantly higher triboelectric output. Moreover, we show the resultant ZIF/PDMS nanocomposite films exhibit enhanced triboelectric properties and long-term stability under cyclic mechanical loading. After integrating the prepared nanocomposite films into TENG devices, we accomplished the peak output voltage and current of 578 V and 19 μA for thin films (3 ×3 cm2, thickness ∼0.33 mm), respectively, by embedding 1 wt % of ZIF-72 nanoparticles into PDMS matrix, with an instantaneous maximum power density of ∼5 W m−2. In this study, the mechanism of improved TENG performance by incorporating MOF nanoparticles has, for the first time, been revealed through nanoscale-resolved mechanical and chemical studies. Furthermore, the practicality of MOF-based TENG was demonstrated by harvesting energy from oscillatory motions, for powering up commercial microelectronics, transmitting electrical signals remotely, and functioning as a self-powered Morse code generator.